THE APPROACH OF SOFT SYSTEMS METHODOLOGY FOR SYSTEM ONLINE MANAGEMENT CONSULTANT CONSTRUCTION - Anisarida, An An; Syapril Janizar; Gary Raya Prima (Dinasti International Journal of Digital Business Management, 2020)
Consultant as a service provider konstrukusi in order to realize its goal to ensure public safety and create a comfort environment of the construction need to organize a system of internal governance of the company. Governance is translated into the stages of the stages in the implementation of Construction Services. Soft Systems Methodology is the methodology suitable to assist the consultant planner. This methodology can explain their purpose and then designing the system of human activity to achieve these goals. The stages that exist in the methodology of SSM consists of 7 stages that starts from the verification problem situation that is not structured through the design of the system of human activity which are expected to help improve the situation. Think the system is a field transdisiplin that appears as a response to the limitations of a technical approach in the process of reduction to solve a certain problem which in this case is attempted to be applied through the SSM as a method in the application of the online management system (OMS) consultant planner construction. Using the approach of Soft Systems Methodology, manufacturing management system online (CSO) will more fully describe the problems that occurred previously.